Analisis Peningkatan Penjualan Ayam Geprek di UMKM Ma’e, Desa Cadasari, Pandeglang, Banten Dengan Menggunakan Metode SWOT - syamsudin syamsudin; Sindy Gefira Rifatunnisa; Siti Fadilah; Tasya Putri Nabila Harahap; Isma Aulia Farozah; Rifki Fauzan Adhiman (Program Studi Teknik Industri Universitas Muhammadiyah Tangerang, 2025)
This study aims to analyze sales improvement strategies for the Ma’e micro, small, and medium enterprise (MSME), which specializes in ayam geprek (smashed fried chicken) and is located in Cadasari Village, Pandeglang Regency, Banten. The approach used in this research is the SWOT method (Strengths, Weaknesses, Opportunities, Threats), which helps identify internal strengths and weaknesses as well as external opportunities and threats faced by Ma’e. Data were collected through direct observation, interviews with the business owner, and customer questionnaires. Based on the SWOT analysis, the X axis score = 3,75 and the Y value = 8,75 from the score results, the position of the MSME is in quadrant I, then the trading strategy is aggressive. The formulation of strategies that can be applied by MSME Ma'e optimizes potential and increases sales. This study is expected to be a reference in making strategic decisions for similar MSME managers in increasing competitiveness and sales.